Low-Frequency noise investigation of AlGaN/GaN high-electron-mobility transistors - Glória Caño de Andrade, Maria [UNESP] (2021)
In this paper, the noise Power Spectral Density (PSD) of AlGaN/GaN High-Electron-Mobility Transistors (HEMTs) has been experimentally investigated in linear operation (VD = 50 mV) for different channel lengths (L) and widths (W) at different temperatures (5.32 °C till 100 °C). The origin of the noise will be analyzed to understand the physical mechanisms involved. It is shown that the Low-Frequency (LF) noise is dominated by 1/f noise, originating from number fluctuations. Additionally, in shorter devices, a higher 1/f noise PSD is found. The LF noise characteristics indicate that the AlGaN/GaN HEMTs on silicon substrates can be a promising candidate for analog and Radio Frequency applications (RF).